Finite-time attitude stabilization of an output-constrained rigid spacecraft. (21st February 2020) - Ma, Jianjun; Li, Peng
This article concentrates on the study of finite-time attitude stabilization for a rigid spacecraft with output constraints. The dynamics of the spacecraft are expressed by modified Rodrigues parameters, so that the singularity of covariance matrix owing to quaternion's redundancy is eliminated. Based on the backstepping technique in combination with adding a power integrator technique, the attitude stabilization control law is constructed. Rigorous mathematical proof shows that the closed-loop system is finite time stable and all the outputs remain bounded by using a barrier Lyapunov function technique. The effectiveness of the proposed finite-time stabilization scheme is verified by a simulation example.